Health insurance coverage in Ethiopia: Financial protection in the Era of sustainable cevelopment goals (SDGs) - Bedasa Taye Merga; Bikila Balis; Habtamu Bekele; Gelana Fekadu (Health Economics Review, 2022)
Background: Health insurance is among the healthcare financing reforms proposed to increase the available healthcare resources and to decrease the risk of household financial crisis. Recently, Ethiopia has been implementing community-based health insurance which mainly targets the very large rural agricultural sector and small and informal sector in urban settings. Therefore, this study was aimed to assess the coverage of health insurance and its determinants in Ethiopia. Methods: Data were extracted from the 2019 mini Ethiopian Demographic and Health Survey (EDHS) to assess determinants of health insurance coverage in Ethiopia. The analysis included a weighted sample of 8663 respondents. Multivariable logistic regression analysis was conducted and the results were presented as adjusted odds ratio (AOR) at 95% confidence interval (CI), statistical significance was declared at a p-value < 0.05 in all analyses. Results: The health insurance coverage in Ethiopia was 28.1% (95%CI: 27.2%, 29%). Administration regions (Tigray: AOR = 16.9, 95%CI: 5.53, 51.59, Amhara: AOR = 25.8, 95%CI: 8.52, 78.02, Oromia, AOR = 4.27, 95%CI: 1.41, 12.92, Southern Nations, Nationalities and Peoples region, AOR = 4.06, 95%CI: 1.34, 12.32, Addis Ababa, AOR = 4.65, 95%CI: 1.46, 14.78), place of residence (rural, AOR = 1.38, 95%CI: 1.17, 1.63), sex of household head (male; AOR = 1.23, 95%CI: 1.07, 1.41), wealth index (middle, AOR = 1.75, 95%CI: 1.46, 2.09, richer, AOR = 1.86, 95%CI: 1.55, 2.24), family size (Ï 5 members, AOR = 1.17, 95%CI: 1.03, 1.33), having under-five children (AOR = 1.22, 95%CI: 1.076, 1.38), and age of household head (31-40 years, AOR = 1.71, 95%CI: 1.45, 2.01, 41-64 years, AOR = 2.49, 95%CI: 2.12, 2.92, 65 + years, AOR = 2.43, 95%CI: 2.01, 2.93) were factors associated with health insurance coverage. Conclusions: Less than one-third of Ethiopians were covered by health insurance. Socio-economic factors and demographic factors were found to associate with health insurance coverage in Ethiopia. Therefore, enhancing health insurance coverage through contextualized implementation strategies would be emphasized.
Keywords: 330; DHS; Ethiopia; Healthcare financing; Insurance